2022
DOI: 10.1093/ehjopen/oeac001
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and cardiovascular disease

Abstract: Endometriosis is a chronic gynecological disease affecting one in ten reproductive-age women. It is defined as the presence of endometrium-like tissue outside the uterus. Beyond this placid anatomical definition, endometriosis is a complex, hormonal, inflammatory, and systemic condition that poses significant familial, psychological, and economic burden. The interaction between the cardiovascular system and endometriosis has become a field of interest as the underlying mutual mechanisms become better understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 131 publications
0
14
0
2
Order By: Relevance
“…The clinical incidence of endometriosis is high, and its main features include dysmenorrhea, dyspareunia, chronic pelvic pain, irregular uterine bleeding and infertility [3], which places a great burden on the economy of health and reduces quality of life in worldwide, 10% of women of reproductive age are diagnosed with endometriosis each year [4]. These patients have higher risks of gynecological cancer (ovarian, endometrial and cervical cancers) [5], polycystic ovary syndrome [6], cardiovascular diseases [7], obesity [8], gestational diabetes mellitus [9], diabetes mellitus [10] and hypertension [11]. Studies have revealed that the progression of endometriosis is related to genetic risk factors [12] as well as environmental factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical incidence of endometriosis is high, and its main features include dysmenorrhea, dyspareunia, chronic pelvic pain, irregular uterine bleeding and infertility [3], which places a great burden on the economy of health and reduces quality of life in worldwide, 10% of women of reproductive age are diagnosed with endometriosis each year [4]. These patients have higher risks of gynecological cancer (ovarian, endometrial and cervical cancers) [5], polycystic ovary syndrome [6], cardiovascular diseases [7], obesity [8], gestational diabetes mellitus [9], diabetes mellitus [10] and hypertension [11]. Studies have revealed that the progression of endometriosis is related to genetic risk factors [12] as well as environmental factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have reported a similar potential association between endometriosis and atherosclerotic CVD, underlying similar pathogenic mechanisms including coronary microvascular dysfunction, endothelial dysfunction and atherogenic lipid profile ( 18 , 19 ). There is an extended amount of literature focusing on the increased risk that women with endometriosis have for developing myocardial infarction, ischemic heart disease, hypertension, atherosclerosis requiring bypass and angioplasty or stenting procedures ( 16 , 20 - 24 ). However, CVD in women with endometriosis remains underdiagnosed and, therefore, detailed studies are required to fully understand the clinical relevance, as well as the underlying pathophysiological mechanisms of the interactions between these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients experience debilitating endometriosis-associated pain that prevents them from usual activities. Chronic inflammation plays a central role in the pathogenesis of atherosclerosis, obesity, diabetes, and hypertension [3], which are often associated with endometriosis [4]. In particular, an increased risk of occurrence of hypertension, gestational hypertension and pre-eclampsia has been reported among women with endometriosis [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation plays a central role in the pathogenesis of atherosclerosis, obesity, diabetes, and hypertension [3], which are often associated with endometriosis [4]. In particular, an increased risk of occurrence of hypertension, gestational hypertension and pre-eclampsia has been reported among women with endometriosis [3][4][5][6]. Several mechanisms, including pro-inflammatory, pro-angiogenic, and aberrant immune-endocrine function, involved in the pathobiology of endometriosis demonstrate compelling associations with cardiovascular disease development.…”
Section: Introductionmentioning
confidence: 99%